A spherical harmonic model of the lithospheric magnetic field of Mars. Issue 6 (9th June 2014) - Morschhauser, A.; Lesur, V.; Grott, M.
Abstract We present a model of the lithospheric magnetic field of Mars which is based on Mars Global Surveyor orbiting satellite data and represented by an expansion of spherical harmonic (SH) functions up to degree and order 110. Several techniques were applied in order to obtain a reliable and well‐resolved model of the Martian lithospheric magnetic field: A modified Huber‐Norm was used to properly treat data outliers, the mapping phase orbit data was weighted based on an a priori analysis of the data, and static external fields were treated by a joint inversion of external and internal fields. Further, temporal variabilities in the data which lead to unrealistically strong anomalies were considered as noise and handled by additionally minimizing a measure of the horizontal gradient of the vertically down internal field component at surface altitude. Here we use an iteratively reweighted least squares algorithm to approach an absolute measure (L1 norm), allowing for a better representation of strong localized magnetic anomalies as compared to the conventional least squares measure (L2 norm). The resulting model reproduces all known characteristics of the Martian lithospheric field and shows a rich level of detail. It is characterized by a low level of noise and robust when downward continued to the surface. We show how these properties can help to improve the knowledge of the Martian past and present magnetic field by investigating magnetic signatures associated with impacts and volcanoes. Additionally, we present some previously undescribed isolated anomalies, which can be used to determine paleopole positions and magnetization strengths.